Adaptation of Independent Curriculum in Remote Elementary Schools: A Field Study in Disadvantaged, Frontier, and Outermost Areas - Sirojuddin, Akhmad; Kartiko, Ari; Ma’arif, Muhammad Anas (LETIGES, 2025)
This study aims to examine how elementary school teachers in remote areas of East Java adapt the Merdeka Curriculum to address local challenges, while also responding to the urgent need to understand how national curriculum policy is interpreted and implemented in the context of Disadvantaged, Frontier, and Outermost (DFO) regions. The study employed thematic analysis, which included stages of data familiarisation, coding, and critical reflection, with data validity ensured through triangulation of interviews, observations, and documentation. The findings reveal three major themes. First, teachers integrated local culture, such as folklore and traditional games, into instruction to enhance relevance and student engagement. For instance, students learned moral values through local hero stories, which enriched their literacy skills. Second, teachers applied project-based learning, such as creating teaching aids from recycled materials to explore environmental issues, fostering student creativity and critical thinking. Third, teachers implemented differentiated instruction by grouping students according to their learning styles, ensuring that each learner received appropriate and inclusive learning experiences tailored to their abilities and needs. This study is limited to several schools in East Java (Sumenep, Sidoarjo, Gresik, and Blitar), which do not fully represent all 3T regions with their diverse cultural and geographical contexts. Moreover, time constraints and limited data accessibility reduced the possibility of more profound exploration of cultural variations and strategies in other areas. Despite these limitations, the study contributes to a better understanding of curriculum localisation and the transformative role of teachers in contextualising the curriculum within challenging environments, while offering practical implications for policymakers, particularly in empowering teachers through locally-based training modules and flexible policies to promote educational equity in remote regions.